Evaluation of soil resistance in Casanare, Colombia (2013)
The this paper contains the results obtained during the interpretation of soil resistiivity data, to the work performed  corresponding in the city of Monterrey, Casanare, Colombia The main objeetive of this research was given to find the optimal point where the grounding of a substation which consists of an electronic system or plant generator or transmitter of radio frequency would by located. The main objective of this reseacrh was given to find the optimal point where the grounding of a substation, which consists of an electronic system or plant generator or transmitter of radio frequency would by located. The paper presents a description of geophysical method of telluric currents, the methodology and the results obtained from 21 points of measurements, in a regular network. It is the resistivity map and map of isolines of the area allowing you to differentiate between different areas.